ANTECEDENT AND KONSEKUEN WORD OF MOUTH - Sugianto, La Ode (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2016)
This research intended to analyze the antecedent and consequent of word of mouth at Sultan Agung Islamic University, Semarang. After distributing the relevant questionnaires to 99 students or research subjects, all usable questionnaires were returned. Then the collected data were analyzed by using Structural Equation Modeling with Smart PLS 3.0 software. Research findings showed that institution image has positive significant effect on word of mouth and students’ loyalty. Furthermore students’ satisfaction has positive significant effect on word of mouth and students’ loyalty. The word of mouth also has positive significant effect on loyalty. Moreover, Islamic academic culture can moderate the correlation between students’ satisfaction and word of mouth in Sultan Agung Islamic University, Semarang.